PENGARUH LINGKUNGAN TEMAN SEBAYA DAN EFIKASI DIRI TERHADAP HASIL BELAJAR EKONOMI - Muhamad Agung Yahya; Yoni Hermawan; Ai Nur Solihat (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine the influence of peer environment and self-efficacy on students' learning outcomes in economics. The research method used is a survey with an explanatory design. The population of this study consists of 118 eleventh-grade students at SMA Negeri 6 in Tasikmalaya who are enrolled in economics. The sample was selected using a saturated sampling technique. Data was collected using questionnaires, and the data analysis technique applied is multiple linear regression. The results show that there is a positive and significant influence of the peer environment on learning outcomes; a positive and significant influence of self-efficacy on learning outcomes; and a positive and significant influence of both learning motivation and peer conformity on learning outcomes.